Perbandingan tingkah laku sosial berdasarkan gender antara generasi muda tinggal di kawasan terpinggir dan arus perdana di Malaysia - Fauziah Ibrahim,; Juliana Rosmidah Jaafar,; Sheau, Tsuey Chong; Koh, Denise Choon Lian (Penerbit Universiti Kebangsaan Malaysia, 2017)
This article aims to compare social behaviors (peer to peer problem, hyperactive behavior, prosocial behavior, behavioral disorder and emotional problem) based on gender (male and female) among young people living in marginalised and mainstream area. This study used quantitative design and cross-sectional approach. A total of 5,237 young people (15-25 years old) were selected as respondents. They were grouped based on their residence area, namely as marginalised and mainstream. For data analysis, t-test was used in this study. Both group in this study were analyzed separately according to respondents’ residence area. For marginalised young people, T-test showed that there were no significant difference in term of gender towards peer to peer problems [t (3556) = 1.62, p = .103] and hyperactive behavior [t (3556) = 1.46, p = .144]. On the other hand, result revealed that there were significant difference in term on gender towards prosocial behavior [t (3556) = 4.85, p = .001], behavioral disorders [t (3556) = 4.83, p = .001] = 3.00, p = .003] and emotional problems [t (3556) = 3.00, p = .003] among these marginalised young people. As for young people in the mainstream area, no significant difference occurred between female and male towards peer to peer problems [t (1667) = 1.10, p = .270], hyperactive behavior [t (1667) = .66, p = .511] and behavioral disorders [t (1667) = .76, p = .449]. However, for this group, significant difference do exist in term of gender towards prosocial behaviors [t (1667) = 2.80, p = .525] and emotional problems [t (1667) = 5.54, p = .001]. These findings have implications on the efforts of stakeholders in developing future programs that can empower social behavior and enhance the development of identity for young generation based on gender living in marginalised or mainstream area in Malaysia.